Temporal-based nurse duty roster system / Masita @ Masila Abd Jalil …[et al.] - Abd Jalil, Masita @ Masila; Ali, Noraida; Ngah, Amir; Ismail, Suryani (2006)
This paper describes the design of a temporal-based Nurse Duty Roster System which uses temporal database to keep all the data and information needed by Sisters at the Hospital. Timestamps are used to make the data available with valid time. Valid time denotes the time period during which a fact is true with respect to the real world. Arrangement of a duty roster is based on the different types of leaves, shift requests, night shifts, on call and wards or units in which the nurses work. In this system, the date is a very important attribute in order to produce a systematic duty roster. The system is developed using Visual Basic 6.0 programming, Crystal Report 8.0 and Microsoft Access 97 as its database.